Involvement of Free Sports for a Healthy Lifestyle: Case Study - E. Dode; M. Shehu; E. Haxhihyseni (University of Sofia, 2020)
Leisure sport activities including extreme sports seem to be selected by youth to promote a healthy lifestyle and other reasons like socialization, communication, making new friends, self-image etc. Researchers share the opinion that among free sports more practiced seems to be the traditional ones, which pose health benefits such as elimination of obesity among young people and adults, reducing stress anxiety, etc. The aim of study is to identify the general level of the practicing of free sports among the young people in Elbasan city. Methodology of the study is based on survey whose questions are adapted to the application ground. Qualitative methods were used to achieve the purpose of the study through interpretive epistemological approach. The study sample among the youth of Elbasan N = 109 age from 18 years to over 27 years, male (N = 15; 13.8%) and females (N = 94; 86.2%). From data analysis Volleyball is exercised by young people (51.4%), approximately one year (28.4%), according to their statements sport practiced in a group sport, friends or other relatives (59.6%), while that emphasize that 14.7% of subjects do not deal with sports. Subjects argue that in exercising free sports had not been influenced by others (63.3%), choices referring to stress management (39.4%), emotional regulation (34.9%), self-esteem increase when dealing with sports activities (42.2%), and to be physically active (75.2%). Subjects assert that, among other activities related to free sport is also watching various sports television programs (45.9%), as well as watching various sports video on the Internet (40.4%). In conclusion, we affirm that young people practice free sport of personal motivation, as helps them among other things, for a better organization of their priorities, leisure, meetings with friends, etc.